The Cebuano translation of the Puthenangady religious motivation review: Its reliability, validity and norms - Canonoy, Susana M. (Animo Repository, 2009)
This study aimed to establish the Cebuano translation of Puthenangady Religious Motivation Review and to strengthen its psychometric properties. It is descriptive in nature, conducted to describe the characteristics of an instrument for assessing religious motivation for priestly/religious life, particularly the Cebuano-Visayan speaking men and women young religious. This thesis study translated the items of the original RMR into Cebuano and had the items back-translated and evaluated for linguistic equivalence to the original version. The Cebuano translation of RMR was administered to 555 Cebuano-Visayan speaking male and female young postulants, novices and simple professed of the 49 different religious congregations and major seminarians of diocesan seminaries of the different parts of the country. The psychometric equivalence of the Cebuano version of the Religious Motivation Review of Puthenangady (1997) was established through this thesis study. All the five factors of the Cebuano version of RMR based on the factor structure of Puthenangady (1997) showed an adequate reliability that ranged from .83 to .92. This study gave evidence of the reliability of the Cebuano equivalence of RMR and the reliability of each factor. The overall reliability of the scale was adequate at r=.88 showing that the test items are internally consistent. The cronbach alpha values as reliability coefficients of the 5 subscales were computed. The data was subjected to factor analysis to re-examine the items and to determine the highest loadings items on the different five factors. In terms of factor structure in the Cebuano RMR, the results reflected almost the same factor structure in the RMR of Puthenangady (1997). 5 Percentile norms for use in interpreting total test scores obtained in the Cebuano RMR; male and female norms were also generated. The study concluded that the Cebuano version of the RMR of Puthenangady(1997) is reliable and valid instrument to be used to assess religious motivation of religious/priestly candidates who are Cebuano-Visayan speaking. Furthermore, the parallelism of factor structures implies that the Cebuano translation is equivalent to the original Puthenangady RMR.